Leucine and protein metabolism in rats with chronic renal insufficiency - Holecek, M; Sprongl, L; Tilser, I; Tichý, M (Experimental and toxicologic pathology, 2001)
The aim of this study was to evaluate the effect of chronic uremia induced by 5/6 nephrectomy (5/6NX) on changes in protein and branched-chain amino acid (BCAA; valine, leucine and isoleucine) metabolism. The control group consisted of sham operated rats. Twenty eight weeks after surgery the parameters of protein and amino acid metabolism were evaluated using a primed constant intravenous infusion of L-[1-(14)C]leucine. A drop in BCAA levels and a significant increase in urea, creatinine and cholesterol were observed in plasma of all 5/6NX rats. However, severe uremia with acidosis developed only in one third of rats with 5/6NX. In 5/6NX rats with acidosis significant increases in proteolysis, leucine oxidation, leucine oxidized fraction, and leucine clearance were observed in comparison with the control group and rats with 5/6NX without acidosis. In addition, in 5/6NX rats with acidosis a significant decrease in valine concentration in gastrocnemius muscle was found. We conclude that marked activation of proteolysis occurs in severe chronic renal failure and is probably caused by metabolic changes related to acidosis development.
Keywords: modely nemocí na zvířatech; proteiny; Male; Rats, Wistar; leucin; Kidney Failure, Chronic; acidóza; přijímání potravy; uremie; chronické selhání ledvin; Valine; Cholesterol; Uremia; Creatinine; Muscle, Skeletal; Isoleucine; Leucine; mužské pohlaví; potkani Wistar; Eating; Body Weight; nefrektomie; kosterní svaly; krysa rodu Rattus; isoleucin; cholesterol; Animals; valin; zvířata; Rats; Disease Models, Animal; kreatinin; močovina; Acidosis; Urea; Nephrectomy; Proteins; tělesná hmotnost